Stability Numbers for Unsupported Conical Excavations in Multi-Layered Cohesive Soils - Kwangwoo Lee; Junyoung Ko; Hyunsung Lim; Joon Kyu Lee (Applied Sciences, 2020)
This paper presents the results of a numerical analysis into undrained stability of conical excavation in multi-layered clays. Stability predictions for a wide range of geometric and material combinations are calculated by finite element analyses. The results from the present analysis are expressed in the familiar form of stability numbers reflecting the effect of (1) angle of inclination, (2) depth ratio, which is relative top layer thickness to excavation depth, (3) strength difference between two layers on the rigid base, (4) width ratio, which is excavation height to radius at the bottom of excavation, and (5) thickness ratio, which is the ratio of the excavation height to thickness of soil 1 layers. The obtained stability numbers are compared with existing solutions published in the literature. The failure mechanism in multi-layered clays are also discussed in terms of the displacement pattern.